Systematic Review and Quality Evaluation of Pharmacoeconomic Studies on Traditional Chinese Medicines - Yang, Nan; Zhang, Huihui; Deng, Taoyi; Guo, Jeff Jianfei; Hu, Ming (Frontiers in Public Health, 2021)
Objectives: This study was aimed to find and appraise the available published pharmacoeconomic research on Traditional Chinese Medicine (TCM), to identify related issues and make suggestions for improvement in future research. Methods: After developing a search strategy and establishing inclusion and exclusion criteria, pharmacoeconomic studies on TCM were sourced from seven Chinese and English databases from inception to April 2020. Basic information about the studies and key pharmacoeconomic items of each study were extracted. The quality of each study was evaluated by using the British Medical Journal economic submissions checklist for authors and peer reviewers, focusing on factors such as study design, research time horizon, sample size, perspective, and evaluation methods. Results: A total of 431 published pharmacoeconomic articles with 434 studies on topics including cost-effectiveness, cost-benefit, cost-minimization, cost-utility, or combination analyses were identified and included in this review. Of these, 424 were published in Chinese and 7 in English. These studies conducted economic evaluations of 264 Chinese patent medicines and 70 types of TCM prescriptions for 143 diseases, including those of the central nervous, cardiovascular, respiratory, gynecologyical, and other systems. The studied TCMs included blood-activating agents (such as Xuesaitong tablet, Fufant Danshen tablet, and Danhong Injection), blood circulation promoting agents (such as Shuxuetong injection, Rupixiao tablet, and Fufang Danshen injection), and other therapeutic agents. The overall quality score of the studies was 0.62 (range 0.38 to 0.85). The mean quality score of studies in English was 0.72, which was higher than that of studies in Chinese with 0.62. Conclusions: The quality of pharmacoeconomic studies on TCM was relatively, generally low. Major concerns included study design, inappropriate pharmacoeconomic evaluation, insufficient sample size, or non-scientific assessment. Enhanced methodological training and cooperation, the development of a targeted pharmacoeconomic evaluation guideline, and proposal of a reasonable health outcome index are warranted to improve quality of future studies.